In Search of the 'Whole Man': Soul-Man-World in the National Socialist Weltanschauung. Issue 3 (2nd September 2017) - Varshizky, Amit
ABSTRACT: This paper examines the Nazi attempt to form a new type of political subject: an ideal type of 'whole man' that would provide an alternative both to Cartesian dualism and to the materialistic vision of 'man a machine' ( l'homme machine ). The paper sets out to elucidate the semantic complexities and the symbolic structures sedimented in the biological language of the Nazis, and thus to examine the ideological and epistemological mechanisms that rendered the apotheosis of the national collectivism in the Third Reich. My argument is that not only did the Nazi attempt to substantiate an 'organic' political community require the redefinition of the relations between the individual and society, but it also required the reconstruction of the human subject itself by redefining his psychophysical composition. As a result, the individual served not only as a political instrument, but also as an ideological one, that is, as 'biological' justification for the Nazi totalitarian structure and its political aspirations.